1974
DOI: 10.1111/j.1432-1033.1974.tb03895.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterisation of Glycoproteins from Sputum

Abstract: Sputum has been separated into a sol and a gel phase by ultracentrifugation and the components of these phases examined. A glycoprotein of high molecular weight as well as serum albumin, immunoglobulin A, sll acid glycoprotein and lactoferrin were detected in the sol phase by gel filtration and immunodiffusion studies. A glycoprotein of similar chemical composition was isolated from the gel phase by solubilisation in 6 M urea/O. 1 M NaCl followed by fractional precipitation with ethanol.The carbohydrate conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

1976
1976
1987
1987

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 52 publications
2
36
0
1
Order By: Relevance
“…,y-Aminobutyric acid (GABA) is widely believed to be the most important chemical mediator of inhibition in the vertebrate central nervous system. The specificity of the inhibitory postsynaptic responses elicited by GABA has suggested that in postsynaptic membranes of GABA-ergic synapses there is a well-defined recognition site for GABA that is coupled with the Cl-ionophore (1). Indeed, binding assay studies using radioactive GABA, crude synaptic membranes, and a Na+-free buffer have shown that GABA recognition sites with characteristics consistent with those expected at postsynaptic sites of GABA-ergic synapses, are present in the mammalian brain (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…,y-Aminobutyric acid (GABA) is widely believed to be the most important chemical mediator of inhibition in the vertebrate central nervous system. The specificity of the inhibitory postsynaptic responses elicited by GABA has suggested that in postsynaptic membranes of GABA-ergic synapses there is a well-defined recognition site for GABA that is coupled with the Cl-ionophore (1). Indeed, binding assay studies using radioactive GABA, crude synaptic membranes, and a Na+-free buffer have shown that GABA recognition sites with characteristics consistent with those expected at postsynaptic sites of GABA-ergic synapses, are present in the mammalian brain (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…It resembles mucins purified by others from several human and animal organs ( I , 4, 6, [17][18][19]. in that it is a polydisperse viscous glycoprotein rich in carbohydrate.…”
mentioning
confidence: 99%
“…Since proteinases in the C F LM-gel samples fragmented radiolabeled tracheobronchial mucin In vitro (Fig. 4), proteinases in LM-gel samples from pathological airways may account for the variations in molecular weight, solubility, and chromatographic behavior reported for tracheobronchial mucins (6,(37)(38)(39)(40)(41)(42)(43)46). This study has also demonstrated that TBM from healthy individuals exhibited physical and chemical properties similar to those of TBM from a patient with bronchial asthma (5).…”
Section: Discussionmentioning
confidence: 59%
“…4) The cysteine contents of the CF lung mucins analyzed were considerably lower than those of normal and asthmatic mucins, and similar to values obtained on analysis of the proteolytically-digested glycopeptide fragments of asthmatic mucin (39,40). However, considerable variability in the cysteine concentrations of tracheobronchial mucins has been reported (5,6,33,(38)(39)(40)(41)(42)(43) and cysteine is often not measured quantitively as it requires almost a mg of purified mucin for accurate measurements in duplicate.…”
Section: Discussionmentioning
confidence: 98%